Glass sheets coated with TiO2-m and its cytotoxic effect on leukemic cells Molt4 (2021)
Photodynamic therapy (PDT) has become an important alternative for the treatment of different types of cancer, due to its great advantages over conventional methods. In this field, TiO2 nanoparticles are one of the most widely studied photosensitizers due to their high photocatalytic activity, high absorption of UVA light and high biocompatibility. Although there are several successful studies related to PDT treatment, using TiO2nanoparticles, for different types of adherent cancer cells, there are few reports of PDT applied to non-adherent cancer cells, due to the challenges related to blood volume and light penetration. To address this challenge, modified TiO2 nanoparticles (TiO2-m) were deposited on glass substrates to study the cytotoxic effect of PDT on Molt4, non-adherent cells, using these coatings. The shaping of uniformed coatings on substrates was proved by standard deviation of transmittance in the UVA range at different points. Different experimental PDT tests of Molt4 cells on TiO2-m coatings were performed and the treatment cytotoxic effect was evaluated by LDH concentration. The results demonstrated the possibility of generating cytotoxic effect on non-adherent cancer cells with only 20 min of contact and 40 min of UVA radiation. This result is the first step for the possible development of new methodologies in the application of PDT on non-adherent cells using TiO2-m coatings